Evaluation of the Educational Environment of Orthopedic Residency Training Programs in Saudi Arabia: A PHEEM-Based Study - Aljuhani W; Mohamed TA; Alanazi A (Advances in Medical Education and Practice)
Wazzan Aljuhani,1– 3 Tarig Awadelkarim Mohamed,4 Abdullah Alanazi1,2 1Department of Orthopedic Surgery, Ministry of the National Guard – Health Affairs, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 3King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4College of Medicine, Department of Medical Education, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaCorrespondence: Abdullah Alanazi, Email a290bd@hotmail.comObjective: This study aimed to assess the quality of the educational environments within which an orthopedic residency training program is being conducted throughout Saudi Arabia and to identify the areas of weaknesses so that the necessary improvements can be made to build a healthy and supportive environment.Methods: This cross-sectional study included all orthopedic residents in Saudi Arabia and was surveyed using the validated Postgraduate Health Educational Environment Measure (PHEEM). We used Google Forms to Email the online survey to Saudi trainees in the orthopedic residency program from January 1 through September 30, 2022.Results: The majority of participants were between 26 and 30 years; 15.6% were women. Among the subscales of PHEEM, perception of role autonomy scores were statistically significantly associated with participants’ regions and their level of training (p = 0.026 and p = 0.019, respectively). The association of perception of teaching and participants’ regions was also statistically significant (p = 0.004). The mean score for the perception of social support subscale was 25.99, which indicates that residents are generally satisfied with the level of support they receive in the training program. However, there is still room for improvement in this area.Conclusion: The overall PHEEM score was positive but highlighted areas for improvement. Role autonomy and instructional subscales were perceived positively, yet still have room for growth. Social support showed more advantages than disadvantages. Despite the generally favorable environment, enhancements are needed in workloads, working hours, clarity of clinical protocols, and teaching supervision quality.Keywords: residency program, orthopedic board, education, evaluation, training